Legal Dilemma in Navigable River Water Pollution: Consequences of Garbage and Baby Diaper Disposal - Qoilun, Nur; Wulandari, Deby Ayu (Reformasi Hukum, 2024)
The pollution of shipping river water due to the disposal of garbage and baby diapers in Tawangsari Village, Sidoarjo Regency, has created a legal dilemma regarding the implementation of existing regulations. Although there are various national and regional regulations regarding waste management, their implementation in the field is still very limited. The research method used is normative juridical law with an empirical approach supported by accidental sampling techniques on eleven residents of Tawangsari Village. The results showed that, many people still do not comply with their obligations and responsibilities in waste management. In addition, weak law enforcement and the lack of waste management facilities at the village level exacerbate the condition. Legal dilemmas arise due to the mismatch between the existence of regulations and the reality on the ground, as well as the inability to balance the provision of appropriate sanctions with community capacity building. This shows that the legal responsibility of both the government and the community has not been maximized. In conclusion, strengthening law enforcement, increasing public awareness, and developing better waste management infrastructure are needed to overcome this legal dilemma. The recommendations of this research are to tighten supervision, provide strict sanctions, and increase education about waste management to the community.